The Evolution of Colonial Legal Regulations in 19th Century Dutch East Indies Classical Literary Texts - fitriany, Aulia; Wahdatur Rike Uyunul Mukarromah; Wibowo, Satrio; Sudrajad, Wahyu; Handayani, Tuti (International Journal of Sustainable Law, 2024)
This study explores the representation of colonial law in 19th-century literary texts, examining how these works reflect and critique the colonial legal system. Using a qualitative approach with content analysis, the research focuses on how colonial law influenced various aspects of indigenous life, including social, cultural, and economic spheres. The study identifies key themes such as colonial law as a tool of oppression, resistance against colonial law, social stratification reinforced by colonial law, and law as a symbol of colonial power. Through literary works like "Hikayat Siti Mariah," "Hikayat Abdullah," and "Syair Perang Mengkasar," the study reveals how these texts serve as both a mirror and critique of colonial legal practices. By analyzing these narratives, the research highlights the role of literature as a social and legal archive, offering alternative perspectives to the official colonial narrative. The study also examines how literary texts document resistance and contribute to an ongoing critique of colonial law, remaining relevant for understanding postcolonial legal dynamics